Bmal1 knockdown suppresses wake and increases immobility without altering orexin A, corticotrophin‐releasing hormone, or glutamate decarboxylase. (14th February 2018) - Akladious, Afaf; Azzam, Sausan; Hu, Yufen; Feng, Pingfu
Summary: Objective: To determine the effect of Bmal1 knockdown (KD) on sleep, activity, immobility, hypothalamic levels of orexin, corticotrophin‐releasing hormone (CRH), and GABAergic glutamate decarboxylase (GAD). Methods: We used Bmal1 siRNA, or control siRNA intracerebroventricular (ICV) injection to knock down Bmal1 in C57BL/6 mice. Sleep polysomnography, wheel‐running activity, and tail suspension test were performed. Polysomnographic (PSG) recordings in both groups were preceded by ICV injection made during both the light phase and the dark phase. We also measured brain orexin A and CRH using an ELISA and measured GAD using immunoblotting. Results: Compared with control group, Bmal1 KD group had reduced wheel activity and increased immobility. Compared with control, the Bmal1 KD group had reduced wheel activity and increased immobility. During the first 24 hours after treatment, we observed that control siRNA induced a much greater increase in sleep during the dark phase, which was associated with lower orexin levels. However, beginning 24 hours after treatment, we observed an increase in sleep and a decrease in time spent awake during the dark phase in the Bmal1 KD group. These changes were not associated with changes in brain levels of orexin A, CRH, or GAD. Conclusion: Bmal1 KD led to reduced activity, increased immobility, and dramatic reduction in time spent awake as well as an increase in sleep during the dark phase. Early after injection, there was a slight change in sleep but brain levels of orexin, CRH, and GAD remain unchanged. Control siRNA also affected sleep associated with changes in orexin levels.